Tailoring copula-based multivariate generalized hyperbolic secant distributions to financial return data: an empirical investigation - Matthias J. Fischer (Friedrich-Alexander-Universität Erlangen-Nürnburg, Lehrstuhl für Statistik und Ökonometrie, 2003)
On of the crucial questions in risk management is how to aggregate individual risk into overall portfolio risk.
Keywords: 330; Skewed hyperbolic secant; Multivariate GHS distribution; Copula